STUDIES ON ANTIMICROBIAL ACTIVITY OF ZIZIPHUS MAURITIANA LAM. - Sivasankari, M.P.; Sankaravadivoo, A. (International Journal of Ayurveda and Pharma Research, 2015)
Ziziphus mauritiana Lam. is a medium sized tree (Rhamnaceae) grows in almost all parts of the country. It is a potent medicinal plant with many biologically active components such as phenolics, flavonoids, triterpenic acids, polysaccharides and saponins. It majorly possesses anti cancer, anti oxidant, wound healing, antifertility, anti inflammatory, antiulcer, antidiahhoreal and antifungal activities. In the present study, anti microbial activity of Ziziphus mauritiana was tested with ethanol and methanol extracts against various medically important bacteria such as Streptococcus pyogenes, Escherichia coli, Staphylococcus aureus, Klebsiella pnemoniae and pathogenic fungi such as Candida albicans and Trichoderma viride. The invitro anti microbial activity was performed by agar well diffusion method. Of the two leaf extracts, ethanol extract from Z. mauritiana leaves exhibited significant antibacterial and antifungal activity. In anti bacterial studies, the results revealed that significant zone of inhibition was observed in ethanol extract of Z. mauritiana leaf against Escherichia coli, Staphylococcus aureus and Klebsiella pnemoniae. In anti fungal studies, ethanol leaf extract showed promising results against Candida albicans and Trichoderma viride.